2008
DOI: 10.1016/j.jcv.2007.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Identification and function of human cytomegalovirus microRNAs

Abstract: AbstractmicroRNAs are an extensive class of non-coding genes that regulate gene expression through posttranscriptional repression. These small RNAs are evolutionarily conserved and are likely to be a basic mechanism of gene regulation present within most eukaryotic organisms. Over 100 viral miRNAs have been identified to date through a combination of bioinformatics and cloning studies. In this review we discuss the use of bioinformatics for the identification of HCMV miRNAs and also for the discovery of potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 52 publications
1
41
0
1
Order By: Relevance
“…The identification of viral miRNAs that are tran-scribed antisense to viral genes is now a well-described feature of known viral miRNAs: proven regulation of antisense targets has been defined for EBV (4), HCMV (24), HSV-1 and -2 (50, 51, 54, 56), and polyomaviruses (47,48). Interestingly, such viral miRNAs do not always regulate their antisense targets by cleavage, as is the case for the simian virus 40 (SV40) miR SV40-miR-S1 and its target, the large T antigen (47), but they may inhibit their targets by the classical translational inhibition model, as is the case for HCMV-miR-UL112-1 and its target, UL114 (24), and putatively the case for HSV-1-miR-H2-3p and its target, ICP0 (54). We therefore hypothesize from these previous observations that HHV-6B could use hhv6b-miR-Ro6-2 and hhv6b-miR-Ro6-3 to downregulate B2 and B1, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The identification of viral miRNAs that are tran-scribed antisense to viral genes is now a well-described feature of known viral miRNAs: proven regulation of antisense targets has been defined for EBV (4), HCMV (24), HSV-1 and -2 (50, 51, 54, 56), and polyomaviruses (47,48). Interestingly, such viral miRNAs do not always regulate their antisense targets by cleavage, as is the case for the simian virus 40 (SV40) miR SV40-miR-S1 and its target, the large T antigen (47), but they may inhibit their targets by the classical translational inhibition model, as is the case for HCMV-miR-UL112-1 and its target, UL114 (24), and putatively the case for HSV-1-miR-H2-3p and its target, ICP0 (54). We therefore hypothesize from these previous observations that HHV-6B could use hhv6b-miR-Ro6-2 and hhv6b-miR-Ro6-3 to downregulate B2 and B1, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed previously that herpesvirus microRNAs downregulate the expression of immediate-early proteins and therefore function in the establishment and maintenance of latency (16,26,42). In the case of MDV2, one microRNA (MDV2-miR-M17) (46) is in an antisense orientation relative to the coding region of MDV2 ICP4 and may potentially target MDV2 ICP4 mRNA for degradation in a manner similar to the mechanism that small interfering RNAs use to effect mRNA degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Viral genes can also be targets for viral microRNAs. In cytomegalovirus (15,16,26) and herpes simplex virus type 1 (42), viral microRNAs have been shown to target immediate-early genes and may play an important role in the establishment and maintenance of latency.…”
mentioning
confidence: 99%
“…For example, miRNAs from Kaposi sarcoma-associated herpesvirus (miRNA K12-11) and gallid herpesvirus 2 (GaHV-2) (MDV-miR-M4) are homologues of the human miRNA mir-155, which is involved in B-and T-cell regulation. Further, miRNAs encoded by EBV, human cytomegalovirus and human herpesvirus 1 (HHV-1) have been implicated in regulating the immediate-early (IE) phase of the viral gene expression cascade and the characteristic herpesvirus processes of latency (Grey et al, 2007;Grey & Nelson, 2008;Murphy et al, 2008;Lu et al, 2008;Umbach et al, 2008). Two recent studies of GaHV-2 have also demonstrated a role for virus-encoded miRNAs in the molecular basis of herpesvirus pathogenicity (Morgan et al, 2008;Xu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%